Legal Implications of Incest Marriage in Balinese Customary Law - Parwati, Ni Putu Ega; Wage Myartawan, I Putu Ngurah Putu; Hadi Saputra, I Nyoman Pasek; Sari Adnyani, Ni Ketut Ni (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aims to discuss incest marriage in terms of marriage law, the legal implications of incest marriage, as well as the problems of customary law and national law governing incest marriage. This study uses empirical juridical research methods with a factual and sociological approach. Incest marriage has violated the provisions contained in Article 8 of Law Number 1 of 1974, Article 30 of the Civil Code, and Article 39 of the Compilation of Islamic Law which prohibits marriage between brothers and sisters who are still related by blood. The legal implications of incest marriage as stipulated in Article 22, Article 24, Article 26, and Article 27 of Law Number 1 of 1974 can be declared null and void. Incest marriage as a tradition that developed in Bonyoh traditional village is not in accordance with national law, but on the other hand customary law in force in the region does not prohibit incest marriage. The indigenous Bonyoh villagers consider incest marriages as an effort to preserve local traditions that have been passed down by ancestors over time